2007
DOI: 10.1038/modpathol.3800757
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative effect of cell-cycle regulators expression on bladder cancer development and biologic aggressiveness

Abstract: The aim of this study was to evaluate the association between p53, p21, p27 and Rb expression, alone or in combination, with pathological features and clinical outcomes of urothelial carcinoma of the bladder. Immunohistochemical staining for p53, p21, p27 and pRB was performed on tissue microarrays comprising normal urothelium from nine controls, transurethral resection specimens from 74 patients with Ta, Tis and/or T1 bladder urothelial carcinoma, radical cystectomy specimens from 226 consecutive urothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
106
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 22 publications
8
106
1
3
Order By: Relevance
“…We and others have previously shown that altered expressions of cyclin E1, p53, pRB, p21, and p27 are independent determinants of prognosis that can act cooperatively/synergistically to promote tumor progression. [19][20][21]24,27 In agreement with these findings, we found that patients with 3 or more altered biomarkers had a statistically and clinically significantly higher risk of disease recurrence or bladder cancer-specific mortality compared with patients with 0-2 altered biomarkers. The choice of the biomarkers was based on previous studies estab- lishing their independent prognostic value in traditional multivariable analyses.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…We and others have previously shown that altered expressions of cyclin E1, p53, pRB, p21, and p27 are independent determinants of prognosis that can act cooperatively/synergistically to promote tumor progression. [19][20][21]24,27 In agreement with these findings, we found that patients with 3 or more altered biomarkers had a statistically and clinically significantly higher risk of disease recurrence or bladder cancer-specific mortality compared with patients with 0-2 altered biomarkers. The choice of the biomarkers was based on previous studies estab- lishing their independent prognostic value in traditional multivariable analyses.…”
Section: Discussionsupporting
confidence: 80%
“…The choice of the biomarkers was based on previous studies estab- lishing their independent prognostic value in traditional multivariable analyses. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Moreover, these biomarkers are commonly used in pathology departments and most pathologists are familiar with immunohistochemical staining and interpretation of these biomarkers. However, combinations of other biomarkers reflecting the functional status of different pathways/phenomena associated with bladder cancer progression may provide similar or even greater predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations